Quantified assessment of 3D nystagmus in BPPV: practical considerations - Kamran Barin; Michelle R. Petrak; Michelle R. Petrak; Amy R. Cassidy; Susan L. Whitney (Frontiers in Neurology)
Patients with posterior canal benign paroxysmal positional vertigo (BPPV) have a characteristic response of torsional-vertical nystagmus after a Dix-Hallpike maneuver. The nystagmus usually has a delayed onset with the intensity increasing rapidly and then subsiding over a relatively short duration of less than 1 min. We recorded horizontal, vertical, and torsional eye movements with a VNG system in 15 patients with case histories consistent with BPPV. The nystagmus response patterns were quantified by the latency, peak nystagmus intensity, duration, rise time, and fall time parameters. The results showed a high degree of variability in the response parameters, which signifies that a typical response pattern is not universal in patients with BPPV. In addition to the torsional-vertical nystagmus response, all patients exhibited different levels of horizontal nystagmus. However, the direction and the timing of the responses were not consistent. Some patients showed nystagmus patterns that lasted much longer than 1 min. Other patients had lower levels of nystagmus in response to the Dix-Hallpike contralateral to the affected side. The differences in response patterns may signify differences in the composition or the placement of otoconia within the canal, which may affect the patient symptoms and the outcome of the repositioning maneuvers. However, some of the variability may reflect how the test is performed and how the eye movements are recorded. The purpose of this study was to demonstrate the need for standardization of nystagmus recording protocols because responses to the Dix-Hallpike maneuver are influenced by many factors such as the gaze direction and whether the measurements are made from the ipsilateral or contralateral eye.